2002
DOI: 10.1007/s00417-001-0421-3
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic abnormalities associated with various types of retinal vein occlusion

Abstract: Our study showed that a variety of hematologic abnormalities may be seen in association with different types of RVO, and any generalization about these disorders applied to all RVO patients may be misleading. The evidence of our study and in the literature indicates that there is no good reason why all patients with RVO should be subjected to extensive, expensive, special hematologic and hypercoagulability investigations, unless, of course, there is some clear indication; the routine, inexpensive hematologic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 66 publications
1
33
2
2
Order By: Relevance
“…I [ 50 ] investigated hematologic abnormalities in 133 (95 major and 38 macular) BRVO patients by routine studies, in 27 platelet aggregation, in 30 antithrombin III, and in 33 α 2 -globulin studies. The fi ndings are discussed at length elsewhere [ 50 ].…”
Section: Hematologic Abnormalitiesmentioning
confidence: 99%
“…I [ 50 ] investigated hematologic abnormalities in 133 (95 major and 38 macular) BRVO patients by routine studies, in 27 platelet aggregation, in 30 antithrombin III, and in 33 α 2 -globulin studies. The fi ndings are discussed at length elsewhere [ 50 ].…”
Section: Hematologic Abnormalitiesmentioning
confidence: 99%
“…Although these 2 entities may share some common cardiovascular and hypercoagulation risk factors, it is important to understand that they are separate entities requiring different management strategies and leading to different complications. Moreover, several studies have suggested that carrying out exhaustive tests for thrombophilia in RVO in the absence of a suggestive medical history is not necessary [1,28,29]. Rehak et al [29] suggested that the role of thrombophilic disorders is much more important in patients without acquired risk factors, i.e.…”
Section: Ocular and Systemic Risk Factorsmentioning
confidence: 99%
“…24 ), I discussed the role of thrombophilia in CRVO and that holds good for hemi-CRVO as well. There, I [ 5 ] critically reviewed the literature about the prevalence of various hematologic abnormalities. I found that the negative fi ndings about the association between those hematologic abnormalities and development of retinal vein occlusion contradicted the positive fi ndings, because of fl aws in the latter studies.…”
Section: Mostly Ischemicmentioning
confidence: 99%